Adaptive evolution of microalgal strains empowered by fulvic acid for enhanced polyunsaturated fatty acid production. (April 2019) - Wang, Xiang; Luo, Shan-Wei; Luo, Wanghaoyun; Yang, Wei-Dong; Liu, Jie-Sheng; Li, Hong-Ye
Graphical abstract: Highlights: Adaptive evolution by fulvic acid and hyposalinity improves algal strains. Fulvic acid enhanced growth and PUFA level of evolved algal strains. Fulvic acid unprecedentedly governs the expression of lipogenic genes. Fulvic acid achieves the highest ever titer of EPA up to 139 μg/mg in evolved strains. Abstract: Microalgae have emerged as the potential source for value-added products such as polyunsaturated fatty acids (PUFAs). Metabolic engineering of multiple metabolic pathways has promoted eicosapentaenoic acid (EPA) production in microalgae, however, further improvement is warranted owing to the burgeoning demand. Here we improved the microalgal strains by adaptive evolution under hyposalinity treatment, which showed that 70% salinity potentiated the algae to enhance PUFAs. To exploit the maximal PUFA production potential of evolved strains, we subjected evolved algae to light, temperature and fulvic acid treatment. Amongst, fulvic acid (15 mg/L) enhanced growth and achieved the highest EPA content (13.9%) in the evolved diatom. Fulvic acid enhanced antioxidant potential and unprecedently governed the expression of PUFA and lipid biosynthetic genes. Collectively, this investigation demonstrates the efficacy of adaptive evolution empowered by fulvic acid and exemplifies a feasible strain improving strategy to harness the biotechnological potential of microalgae.